Metáforas no pensamento e no discurso: uma análise cognitivo-discursiva da fala de aprendizes de inglês língua estrangeira sobre sua experiência de aprendizagem - Thiago da Cunha Nascimento (2016)
This thesis aims to investigate the metaphors in the speech of English as Foreign Language (EFL) learners and their conceptualizations concerning the aspects involved in the process of learning such a language, for instance, their motivations to study the language, their perception of English language, the role of language teachers, exchange programs possibilities etc. We have adopted a theoretical and analytical perspective of two theoretical frameworks that in our view complement each other, namely the cognitive metaphor theory and the metaphor discursive approach, in order to analyse the speech of EFL students. This study falls within an interpretative-qualitative paradigm due to its case-study method and the use of the focus group technique for data collection, as well as its explanatory, descriptive and interpretative features. Our corpus comprises two focus groups, each formed by six individuals who are EFL students of the Centro de Extensão da Faculdade de Letras of Minas Gerais Federal University in Brazil. One focus group consisted of advanced learners and the other, of elementary ones. The audio and video recordings were transcribed into intonation units (Chafe, 1994), according to the transcription orientations by Stelma and Cameron (2007). A cognitive analysis of the data, based on the Conceptual Metaphor Theory (Lakoff and Johnson, 2003 [1980], 1999; Johnson, 1987, 2007; Gibbs, 2005), was conducted, so that we could approach the cognitive metaphors and other thinking figures present in the learners speech. We also enjoyed the chance to carry out a metaphor-led discourse analysis (Cameron, 2003, 2007b; Cameron et al., 2009; Cameron and Maslen, 2010) in order to investigate discursive metaphors and other phenomena such as image schemas and metonymies (Gibbs, 1994, 2005) which occurred in the learners speech. We found out that pre-linguistic schemas such as FORCE, OBJECT, CONTACT, SOURCE-PATH-GOAL and CONTEINER structure some linguistic expressions concerning the experience of English learning. It was also identified conceptual metaphors such as MOTIVATION IS COMPULSORY FORCE, LANGUAGE IS AN OBJECT, ENGLISH LEARNING IS A JOURNEY and ENGLISH TEACHER AS A BUILDER, underlying linguistic expressions used to talk about Topics like motivation for learning English, English language, English learning and English teacher respectively. Regarding the discursive scope, we verified the emergence of MOTIVATION FOR LEARNING ENGLISH IS TO BE FORCED BY SOCIETY, ENGLISH LANGUAGE IS AN OBJECT YOU POSSESS and TEACHERS ACTIONS ARE COMPELLING FORCES OR INHIBITING FORCES IN LEARNING PROCESS systematic metaphors, for instance, referring to motivation for learning English, English language and English language, the Topics of the conversation.